PSYCHOLOGICAL AND PEDAGOGICAL ESSENCE OF SOCIAL COMMUNICATIVE ACTIVITY OF PERSONALITY - L.V. Petko (Academy of Cognitive and Natural Sciences, 2022)
The article is discovered psychological and pedagogical content of concept "social - communicative activity ". This work contains theoretical and experimental research of this phenomenon.